On-treatment blood pressures of older hypertensive patients in Canada: implications for Systolic blood PRessure INtervention Trial. Issue 3 (March 2017) - Fodor, Jiri George; Baker, Penelope; Chen, Li; Leenen, Frans H.H.
Abstract : Objective: The therapeutic target level for the blood pressure (BP) on antihypertensive drug treatment in older hypertensive patients is still extensively debated. We assessed the achieved BP levels in older treated hypertensive patients in a representative sample of the population. Design: During the 2006 Ontario Survey on the Prevalence and Control of Hypertension, BP (using the SPRINT protocol) and treatment data were collected in 2551 respondents from a random and representative sample of the adult (20–79 years) population. Responses are weighted to the Ontario hypertensive population of 1367 384, of which 684 928 were in the 60–79-year age range. Results: Among 60–79-year-old individuals, using traditional definitions the prevalence of hypertension was 49%. Hypertension treatment rates were high (85%) as were control rates among treated hypertensive patients (85% for 60–69-year-old and 70% for 70–79-year-old patients). A total of 38% of older hypertensive patients were treated with a single antihypertensive drug. A total of 54% of these had a SBP less than 130 mmHg and 23% less than 120 mmHg. Of those treated with combination therapy, 75% had a SBP less than 130 mmHg, and 44% had a SBP less than 120 mmHg. For treated and controlled hypertensive patients, average SBP was 120 mmHg for the 60–69-year age groups, and 119 mmHg in the 70–79-year age groups. Conclusion: These findings suggest that intensive BP control, now being considered for high-risk hypertensive patients based on results from SPRINT, was actually already being achieved ∼10 years ago in a large section of the general hypertensive population of Ontario, Canada.